(untitled) (Journal of Scientific Research, 2026)
Pseudomonas aeruginosa is a major cause of burn wound infections, often exhibiting multidrug resistance. This study evaluated the antibiotic and antiseptic susceptibility patterns of P. aeruginosa isolated from burn patients. Burn wound swabs (n = 30) were collected prospectively and cultured on cetrimide agar. Isolates were identified by cultural, morphological, and biochemical tests. Antibiotic susceptibility was determined using the Kirby-Bauer disc diffusion method against 16 antibiotics, while antiseptic susceptibility was assessed by agar cup method against Hexisol, 70 % ethanol, Dettol, and Savlon. Out of 30 samples, 12 were culture positive and 6 yielded P. aeruginosa. All isolates were susceptible to colistin; however, the majority of tested antibiotics - including streptomycin, ciprofloxacin, nalidixic acid, cephalosporins, cotrimoxazole, amoxiclav, and nitrofurantoin - showed limited or no effectiveness. The multiple antibiotic resistance (MAR) index ranged between 0.75 and 1.00, reflecting high selective pressure from antibiotic exposure. Among the antiseptics tested, Hexisol demonstrated the strongest bactericidal activity, whereas 70% ethanol, Dettol, and Savlon exhibited comparatively lower efficacy. These results indicate that P. aeruginosa isolates from burn wounds display extensive drug resistance, along with reduced susceptibility to commonly used antiseptics. Enhanced infection control measures and judicious antibiotic use are crucial to limit the dissemination of these resistant pathogens in healthcare facilities.